Pediatric Anti-N-Methyl-d-Aspartate Receptor Encephalitis: A Review with Pooled Analysis and Critical Care Emphasis - Kenneth E. Remy; Kenneth E. Remy; Kenneth E. Remy; Jason W. Custer; Joshua Cappell; Cortney B. Foster; Nan A. Garber; L. Kyle Walker; Liliana Simon; Dayanand Bagdure (Frontiers Media S.A., 2017)
PurposeAnti-N-methyl-d-aspartate receptor (NMDAR) encephalitis is being recognized with increasing frequency among children. Given the paucity of evidence to guide the critical care management of these complex patients, we provide a comprehensive review of the literature with pooled analysis of published case reports and case series.MethodsWe performed a comprehensive literature search using PubMed, Scopus, EMBASE, and Web of Science for relevant published studies. The literature search was conducted using the terms NMDA, anti-NMDA, Anti-N-methyl-d-aspartate, pediatric encephalitis, and anti-NMDAR and included articles published between 2005 and May 1, 2016.ResultsForty-eight references met inclusion criteria accounting for 373 cases. For first-line treatments, 335 (89.8%) received high-dose corticosteroids, 296 received intravenous immunoglobulin (79.3%), and 116 (31%) received therapeutic plasma exchange. In these, 187 children (50.1%) had a full recovery with only minor deficits, 174 patients (46.7%) had partial recovery with major deficits, and 12 children died. In addition, 14 patients were reported to require mechanical ventilation.ConclusionAnti-NMDA encephalitis is a formidable disease with great variation in clinical presentation and response to treatment. With early recognition of this second most common cause of pediatric encephalitis, a multidisciplinary approach by physicians may provide earlier access to first- and second-line therapies. Future studies are needed to examine the efficacy of these current therapeutic strategies on long-term morbidity.